Comparison of various approaches to detect algal culture contamination: a case study of Chlorella sp. contamination in a Phaeodactylum tricornutum culture - Grivalský, Tomáš; Střížek, Antonín; Přibyl, Pavel; Lukavský, Jaromír; Čegan, Radim; Hobza, Roman; Hrouzek, Pavel (Applied microbiology and biotechnology, 2021)
Microalgal contamination in algal culture is a serious problem hampering the cultivation process, which can result in considerable economic and time losses. With the field of microalgal biotechnology on the rise, development of new tools for monitoring the cultures is of high importance. Here we present a case study of the detection of fast-growing green algae Chlorella vulgaris (as contaminant) in a diatom Phaeodactylum tricornutum culture using various approaches. We prepared mixed cultures of C. vulgaris and P. tricornutum in different cell-to-cell ratios in the range from 1:103 to 1:107. We compared the sensitivity among microscopy, cultivation-based technique, PCR, and qPCR. The detection of C. vulgaris contamination using light microscopy failed in samples containing cell ratios <1:105. Our results confirmed PCR/qPCR to provide the most reliable and sensitive results, with detection sensitivity close to 75 cells/mL. The method was similarly sensitive in a pure C. vulgaris culture as well as in a mixed culture containing 107-times more P. tricornutum cells. A next-generation sequencing analysis revealed a positive discrimination of C. vulgaris during DNA extraction. The method of cultivation media exchange from sea water to fresh water, preferred by the Chlorella contaminant, demonstrated a presence of the contaminant with a sensitivity comparable to PCR approaches, albeit with a much longer detection time. The results suggest that a qPCR/PCR-based approach is the best choice for an early warning in the commercial culturing of microalgae. This method can be conveniently complemented with the substitution-cultivation method to test the proliferating potential of the contaminant. KEY POINTS: • PCR-based protocol developed for detection of Chlorella cells. • Synergy of various approaches shows deeper insight into a presence of contaminants. • Positive/negative discrimination occurs during DNA extraction in mixed cultures. • Newly developed assays ready to use as in diagnostics of contamination.
Keywords: rozsivky; biotechnologie; Chlorella; Methods; Fresh Water; Biotechnology; Biomass; mikrořasy; sladká voda; Diatoms; Microalgae; Contamination detection; Chlorella vulgaris; Phaeodactylum tricornutum; biomasa